Breaking the mould in patient safety. (29th June 2009) - Degos, Laurent; Amalberti, René; Bacou, Jean; Carlet, Jean; Bruneau, Charles
Abstract : To achieve real improvements in patient safety we need to look at the whole of patients' care not just specific procedures, argue Laurent Degos and colleagues